Effect of parboiling on in vitro physiological antioxidant capacity of brown rice - Lee, Elaine; Neoh, Phene Pei Nee; Lee, Huei Hong; Wong, Sie Chuong; Wong, Tze Jin; Koo, Lee Feng; Yiu, Pang Hung (Universiti Putra Malaysia Press, 2019)
Parboiling process has been widely implemented in brown rice processing, but its effect on in vitro physiological antioxidant capacity of brown rice was not known. In this study, an in vitro method simulating the human physiological conditions was used to investigate the effect of parboiling on antioxidant capacity of brown rice in three Bario rice varieties. In this method, bacterial inocula were prepared from rat cecal contents. Results showed that parboiling process gave significant impacts on in vitro physiological antioxidant capacity of brown rice. The process improved total phenolic content at small intestine (Adan Halus), DPPH scavenging activity at both small and large intestines (Adan Halus and Bario Merah) and ferrous ion-chelating activity at large intestine (Bario Hitam). However, changes in antioxidant capacity were variety dependent, possibly due to different bran pigmentation. These suggested that parboiling process could improve physiological antioxidant capacity with in vitro simulation at small and large intestines by selecting a suitable rice variety and parboiled brown rice could offer good antioxidant properties to maintain physiological health.